Federated States of Micronesia : Staff Report for the 2002 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This 2002 Article IV Consultation highlights that the economic activity in the Federated States of Micronesia (FSM) is estimated to have slowed. Despite the use of the bump-up funds by some of the FSM's four state governments to boost spending during FY2002, GDP is estimated to have grown only by 0.8 percent. The fiscal stimulus appears to have been mostly offset by an emerging fiscal crisis in Chuuk and a 'wait and see' attitude of the private sector in the face of uncertainty associated with the new Compact of Free Association.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet